A hexacyanomanganate negolyte for aqueous redox flow batteries - Jang, Ji-Eun (2024)
Aqueous redox flow batteries (RFBs) have emerged as promising large-scale energy storage devices due to their high scalability, safety, and flexibility. Manganese-based redox materials are promising sources for use in RFBs owing to their earth abundance, affordability, and variety of oxidation states. However, the instability of Mn redox couples, attributed to the unstable d-orbital configuration of Mn3+(d4) known to involve strong Jahn-Teller effects, has hindered their practical use. Here, we discover that the [Mn(CN)6]5-/4-/3- negolyte offers advantages in terms of reversibility, stability, and reaction kinetics owing to the addition of NaCN supporting electrolyte, which inhibits ligand exchange reactions, resulting in high performance. [Mn(CN)6]5-/4-/3- negolyte possesses stable multielectron reactions from Mn(I) to Mn(III), leading to a high capacity of 133.7 mAh after 100 cycles. We provide chemical evidence obtained from in situ Raman analysis for unprecedented Mn(I) stability during electrochemical cycling, opening up new avenues for the design of low-cost Mn-based redox systems.